Effects of a high protein, whey protein concentrate and spray-dried animal plasma on growth performance of weanling pigs - G S Grinstead; J C Woodworth; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1997)
A 35-d experiment was conducted to compare the effects of increasing spray-dried animal plasma and a high protein whey concentrate (73% CP) on starter pig performance. Spray-dried animal plasma and whey protein concentrate replaced dried skin1 milk on an equal lysine basis. Pigs fed increasing spray-dried animal plasma protein had increased ADG and ADFI from d 0 to 7 after weaning, but not for any other period in the study. Increasing whey protein concentrate had no effect on growth perforn1ance in relation to the pigs fed dried skim milk.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Starter pigs; Spray-dried animal plasma; Whey protein concentrate